The Influence of Pancasila and Citizenship Education Learning on Critical Thinking at Tandun 1 State High School - Putri, Linda Rahmawati; Arianto, Jumili; Hardian, Mirza (Jurnal Pendidikan Amartha, 2024)
This research is motivated by the lack of student motivation to learn which is still low. The research results show that learning motivation is very important and can influence critical and creative thinking. This research aims to find out whether learning Pancasila education has an effect on the critical thinking skills of students at SMA Negeri 1 Tandun. This research was carried out using quantitative methods with a casual associative approach, and involved students of SMA Negeri 1 Tandun as research subjects. The data collection instrument used was conventional, and the IBM SPSS Version 22 application was used for data processing. Based on the results of the analysis, a simple linear regression equation was obtained, namely Ŷ= 14,245 + 0.629 Meanwhile, the results of the t test obtained t_count of 14.245 t_table of 2.00, which shows that so that Ho is rejected and Ha is accepted. So this research hypothesis is accepted that there is an influence of Civics Learning on Critical Thinking Ability.